Utilization of Pineapple (Ananas comosus) Skin Waste as an Antioxidant for Constipation Medicine - Aminina, Aminina (Jurnal EduHealth, 2025)
Pineapple peel (Ananas comosus L. Merr), which has been considered as waste, actually contains various active compounds that have potential as herbal medicine ingredients. One of its main benefits is its ability as a natural antioxidant that can ward off free radicals, as well as support digestive function.This study aims to assess the potential of pineapple peel as a source of antioxidants and as a natural remedy for constipation. The content of bromelain, dietary fiber, vitamin C, and phenolic compounds in it is known to have biological activities that support smooth bowel movements. The research method used a quantitative descriptive approach by distributing questionnaires to respondents to determine public perceptions of pineapple peel utilization. The results showed that most respondents believed in the effectiveness of pineapple peel in overcoming constipation. The percentage of constipation sufferers was higher in women (40%) than men (30%), indicating a tendency for greater vulnerability in women. In conclusion, pineapple peels have the potential to be an effective alternative herbal treatment in reducing constipation symptoms while increasing the use value of organic waste.